Significance of imaging findings in the diagnosis of heterotopic spleen—an intrapancreatic accessory spleen (IPAS): Case report. Issue 52 (December 2017) - Yang, Bin; Valluru, Bimbadhar; Guo, Ya-ru; Cui, Chunmao; Zhang, Ping; Duan, Wenshuai
Abstract: Rationale: Accessory spleen (Heterotopic/Ectopic) or splenunculus has been attributed to the failure of the fusion of splenic primordial buds-derived from dorsal mesentery (mesodermal mesenchymal in origin) during the 5th week of embryonic organogenesis or to an extreme degree of splenic lobulation with pinching off of the spleen tissue. The most common locations for accessory spleens are the hilum of the spleen followed by adjacent to the tail of the pancreas. The patients usually present with no clinical symptoms. Patient concerns: A 49-year-old female undergoing a routine medical examination- Abdominal Ultrasound revealed a pancreatic mass. She was admitted into the hospital for 3 days and was put under observation. There are no specific findings during the physical examination or any related abnormalities in the laboratory investigations. Diagnosis: Heterotopic spleen—an intrapancreatic accessory spleen (IPAS). Interventions: Noncontrast CT of the abdomen demonstrated a soft tissue mass with a clear boundary in the tail of the pancreas. On contrast examination—the arterial phase, it was markedly enhanced, homogenous congruity similar to that of spleen; on magnetic resonance imaging (MRI)-T2WI with fat suppressed sequence, it demonstrated a regular round clear edged mass in the pancreatic tail. On Diffusion Weighted Imaging (DWI), a mass with a clear boundary was observed within the parenchyma of the pancreatic tail. The mass showed a high signal on noncontrast MRI, while on contrast examination, the mass showed a strengthening signal with homogenous enhancement as that of spleen. Outcomes: Heterotopic spleen presentation is a very rare asymptomatic clinical condition. During the routine medical examination - it presents mostly as a solitary benign round or oval mass with a clear boundary or as an ectopic focus, either in the pancreatic tail or adjacent to the pancreatic appendage, as an incidental finding. On Contrast CT, it shows as a homogeneously enhanced density- a strengthening mass lesion, in the pancreatic tail, similar to that of spleen. Lessons: Our case emphasizes the importance of recognizing IPAS radiological characteristics and typical variations in its presentation in an asymptomatic patient that could help the personnel to differentiate it from other mass lesions. Thus, recognizing imaging findings on Plain CT, Contrast CT and MRI plays a key role to form a conclusive diagnosis of an accessory spleen, which has to be clinically associated. So, surgeons should consider IPAS as a differential for which unnecessary resection and an unintended surgical procedure can be avoided.